Isomorphic Response Following Laser Tattoo Removal - Matthew Solomon; Jessica May Franklin; Jared Roberts; Chad Hivnor (Lasers in Surgery and Medicine, 2026)
ABSTRACT Objectives We present a case of Koebnerized psoriasis following laser tattoo removal, a scenario that has not yet been reported in the current literature. Methods A 39‐year‐old male with plaque psoriasis was treated for tattoo removal with picosecond and CO2 laser therapies. He had two sessions of combined picosecond and CO2 treatments and one session of picosecond alone. Results One month after the third session, he developed psoriasiform changes at the treated sites, consistent with an isomorphic response, and this was confirmed on histopathological examination. Conclusions This case is significant as Koebnerization after laser tattoo removal is not reported in the literature. It raises important considerations regarding the role of laser‐induced dermal inflammation and the impact of tattoo pigments on psoriatic responses. The findings highlight the potential for laser therapies to exacerbate preexisting conditions like psoriasis, emphasizing the need for careful patient evaluation prior to treatment.